2021
DOI: 10.1109/tcbb.2021.3076259
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Binding Sites on SARS-CoV-2 Spike Protein Receptor-Binding Domain by Molecular Dynamics Simulations in Mixed Solvents

Abstract: The novel SARS-CoV-2 uses ACE2 (Angiotensin-Converting Enzyme 2) receptor as an entry point. Insights on S protein receptor-binding domain (RBD) interaction with ACE2 receptor and drug repurposing has accelerated drug discovery for the novel SARS-CoV-2 infection. Finding small molecule binding sites in S protein and ACE2 interface is crucial in search of effective drugs to prevent viral entry. In this study, we employed molecular dynamics simulations in mixed solvents together with virtual screening to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Pyrimidine (Py), acetonitrile, and isopropanol were used to discover possible docking niches on the interface between RBD and ACE2, and to inspire the drug design of antagonists or antibodies. [ 57 ] Py showed the most relevant volumetric maps within the RBD that spans from residue Gln498 to residue Tyr505. Knowledge of these types of interactions, in conjunction with the molecular mechanics with generalized Born surface area solvation (MM‐GBSA) analysis, leads drug design processes and virtual screening in concordance with experimental data from antibodies, with the data suggesting a set of new molecules (DB02651, DB03714, DB08248, and DB14826) as possible RBD interaction modulators.…”
Section: Hide and Seek: The Hunt For Epitopes Through MDmentioning
confidence: 99%
“…Pyrimidine (Py), acetonitrile, and isopropanol were used to discover possible docking niches on the interface between RBD and ACE2, and to inspire the drug design of antagonists or antibodies. [ 57 ] Py showed the most relevant volumetric maps within the RBD that spans from residue Gln498 to residue Tyr505. Knowledge of these types of interactions, in conjunction with the molecular mechanics with generalized Born surface area solvation (MM‐GBSA) analysis, leads drug design processes and virtual screening in concordance with experimental data from antibodies, with the data suggesting a set of new molecules (DB02651, DB03714, DB08248, and DB14826) as possible RBD interaction modulators.…”
Section: Hide and Seek: The Hunt For Epitopes Through MDmentioning
confidence: 99%
“…Pyrimidine (Py), acetonitrile, and isopropanol were used to discover possible docking niches on the interface between RBD and ACE2, to inspire the drug design of antagonists or antibodies. [44] Py showed the most relevant volumetric maps within the RBM that spans from residue Gln498 to residue Tyr505. Knowledge of these types of interactions, in conjunction with molecular mechanics with generalised Born surface area solvation (MM-GBSA) analysis, lead drug design processes and virtual screening in concordance with experimental data from antibodies, has suggested a set of new molecules (DB02651, DB03714, DB08248 and DB14826) as possible RBD interaction modulators.…”
Section: Hide and Seek: The Hunt For Epitopes Through MDmentioning
confidence: 99%
“…This was done by measuring distances between chosen atoms. 16,18 Rauhamaki et al used sdfconf to generate a simple pharmacophore filter to refine docked conformations. Sdfconf was used to select only conformations without hydrophobic groups in proximity of a certain side chain atom.…”
Section: Importing External Data To Metadata (By Molecule)mentioning
confidence: 99%
“…More examples of how sdfconf has been utilized in research can be found from recent studies. For example, classification of molecules/conformations based on any property and importing and exporting data into metafields have been used extensively. Kurkinen et al used sdfconf to calculate the average geometric centroids for the top-ranked docking poses .…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation